Low-Light Anoxygenic Photosynthesis and Fe-S-Biogeochemistry in a Microbial Mat - Haas, Sebastian; de Beer, Dirk; Klatt, Judith M.; Fink, Artur; Rench, Rebecca McCauley; Hamilton, Trinity L.; Meyer, Volker; Kakuk, Brian; Macalady, Jennifer L. (Frontiers in Microbiology, 2018)
We report extremely low-light-adapted anoxygenic photosynthesis in a thick microbial mat in Magical Blue Hole, Abaco Island, The Bahamas. Sulfur cycling was reduced by iron oxides and organic carbon limitation. The mat grows below the halocline/oxycline at 30 m depth on the walls of the flooded sinkhole. In situ irradiance at the mat surface on a sunny December day was between 0.021 and 0.084 µmol photons m-2 s-1, and UV light (<400 nm) was the most abundant part of the spectrum followed by green wavelengths (475-530 nm). We measured a light-dependent carbon uptake rate of 14.5 nmol C cm-2 d-1. A 16S rRNA clone library of the green surface mat layer was dominated (74%) by a cluster (>97% sequence identity) of clones affiliated with Prosthecochloris, a genus within the green sulfur bacteria (GSB), which are obligate anoxygenic phototrophs. Typical photopigments of brown-colored GSB, bacteriochlorophyll e and (β-)isorenieratene, were abundant in mat samples and their absorption properties are well-adapted to harvest light in the available green and possibly even UV-A spectra. Sulfide from the water column (3-6 µmol L-1) was the main source of sulfide to the mat as sulfate reduction rates in the mats were very low (undetectable-99.2 nmol cm-3 d-1). The anoxic water column was oligotrophic and low in dissolved organic carbon (175-228 µmol L-1). High concentrations of pyrite (FeS2; 1-47 µmol cm-3) together with low microbial process rates (sulfate reduction, CO2 fixation) indicate that the mats function as net sulfide sinks mainly by abiotic processes. We suggest that abundant Fe(III) (4.3-22.2 µmol cm-3) is the major source of oxidizing power in the mat, and that abiotic Fe-S-reactions play the main role in pyrite formation. Limitation of sulfate reduction by low organic carbon availability along with the presence of abundant sulfide-scavenging iron oxides considerably slowed down sulfur cycling in these mats.